The Impact of COVID-19 on Souvenir Industry in Marine Tourism Areas in Indonesia - Arumsari, Indah Pambudi; Yosintha, Rolisda (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
Covid-19 is a lethal virus that is being faced by the world. Many sectors are affected by the virus, including the marine tourism industry and all people who work in this industry. This study aimed to investigate the impact of Covid-19 on souvenir traders in the marine tourism area in Indonesia. The researchers used a qualitative method to collect the data and descriptive analysis to analyze the data. The findings show that Covid-19 has detrimentally affected souvenir traders in marine tourism areas in Indonesia as they lost nearly 100% of their income from tourist visits. To overcome this income deficit, most of them choose to switch professions to become farmers, fishermen, seaweed farmers, and antiseptic gel makers